2012
DOI: 10.1115/1.4007570
|View full text |Cite
|
Sign up to set email alerts
|

An Explanation for Flow Features of Spike-Type Stall Inception in an Axial Compressor Rotor

Abstract: The unsteady behavior and three-dimensional flow structure of spike-type stall inception in an axial compressor rotor were investigated by experimental and numerical analyses. Previous studies revealed that the test compressor falls into a mild stall after emergence of a spike, in which multiple stall cells, each consisting of a tornado-like vortex, are rotating. However, the flow mechanism from the spike onset to the mild stall remains unexplained. The purpose of this study is to describe the flow mechanism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 15 publications
3
37
0
Order By: Relevance
“…In Ref. [6], the same result can be drawn with circumferential located pressures of spike-type stall precursors. In Ref.…”
Section: Introductionsupporting
confidence: 66%
“…In Ref. [6], the same result can be drawn with circumferential located pressures of spike-type stall precursors. In Ref.…”
Section: Introductionsupporting
confidence: 66%
“…Vo et al [5] suggested two criteria necessary for spike-type stall-inception. Yamada et al [6] also suggested that leading edge separation and a tornado-like separation vortex mainly influenced the spike-type stall inception. März et al [4] found that the rotating instability was induced by the interaction between the incoming flow, the reversed tip-leakage flow, and the end wall backflow from the trailing edge of the rotor blade.…”
Section: Introductionmentioning
confidence: 99%
“…In the experimental and numerical work of Yamada et al [22], the low-pressure region near the casing wall during stall inception was concluded to be caused by a tornado-like separation vortex resulting from a leading-edge separation from the suction surface at the rotor tip.…”
mentioning
confidence: 97%